Deep-black is the new green: Europe-India Innovation Pathways in Laser Systems for Space-Debris Reduction - Carrera, Andrea; Baumert, Thomas (Papeles de Europa, 2025)
The expansion of the new space economy has amplified the threat posed by orbital debris. This article maps the global value chains (GVCs) behind Europe’s laser-based technologies for debris detection and mitigation, focusing on European Space Agency (ESA) and private sector systems. The analysis highlights Europe’s dependence on semiconductor-based laser components. The article also examines the strategic potential of cooperation between ESA and the Indian Space Research Organisation (ISRO) in the fight against space debris. India’s strengths in software development, systems integration, and cost-effective innovation complement Europe’s hardware capabilities. The study concludes that strengthened ESA-ISRO collaboration could enhance debris-mitigation capacities while reinforcing the resilience of GVCs supporting laser-ranging technologies.